2022
DOI: 10.1017/sjp.2022.8
|View full text |Cite
|
Sign up to set email alerts
|

Leader Extraversion as a Boundary Condition in the Relationship between Transformational Leadership, Vitality, and Job Improvement

Abstract: We examine the relationship between transformational leadership and job improvement behaviors by considering the moderating effect of leader extraversion and the mediating role of employee vitality. Multi-level path analysis on data from 101 leaders and 619 subordinates provided support to the moderating effect of leader extraversion, such that the relationship between transformational leadership and employee vitality is stronger when the level of leader extraversion is high. Moreover, a moderated mediation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Similarly, prior research indicated the moderating role of extraversion in the relationship between agentic threats and support-seeking behaviors ( Pow et al, 2017 ). Moreover, Lajoie et al (2022) found that a leader’s extraversion functions as an enhancer in the linkage between transformational leadership and follower vitality.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Similarly, prior research indicated the moderating role of extraversion in the relationship between agentic threats and support-seeking behaviors ( Pow et al, 2017 ). Moreover, Lajoie et al (2022) found that a leader’s extraversion functions as an enhancer in the linkage between transformational leadership and follower vitality.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%